The particle century - Fraser, Gordon (Institute of Physics Pub., 2011)
From the first attempts to split the atom to the discovery of the top quark, the 20th century has witnessed a revolution in basic physics. Probing successively smaller constituents of matter has also revealed the conditions present at the time of the Big Bang. In a series of essays by scientists who have been closely involved in this exciting research, The Particle Century describes the unprecedented advances in our understanding of the universe. The book covers major historical developments as well as current advances, including early accelerator physics, the rise of the Standard Model, new comprehension of the big bang theory, and the cutting edge of today's investigations. These essays add novel insight into the continuing efforts to unravel the deepest secrets of nature.